Concentrations of indolebutyric acid on air-layering of guava cv. Paluma - Tamwing, Gabriela da Silva; Elviro de Araújo Neto, Sebastião; de Almeida Rodrigues, Isabela; Ferreira de Oliveira, Rosely; Jhosef de Souza, Bruno; Barbosa Mota, Bárbara (Comunicata Scientiae, 2020)
Nowadays, the predominant technique for the commercial propagation of guava seedlings is through cuttings, using herbaceous cuttings that need a specialized infrastructure with intermittent misting, clean water, exhausters, water filters, and fans. As an alternative to plant propagation by cuttings, this study aimed to evaluate the influence of concentrations of indolebutyric acid (IBA) on the rooting of branches of the guava cv. Paluma by air-layering. The experimental design was in randomized blocks, with four replications and 10 air layers per plot. The treatments consisted of six concentrations of IBA powder mixed with industrial talcum: 0, 1,000, 2,000, 3,000, 4,000, and 5,000 mg.kg-1. Four adult guava parents that were in the off-season period were used. For the preparation of the air layers, the stems were girdled with a 4.0 cm width, using a steel blade, by removing the bark until exposing the cambium region, followed by IBA application and wrapping of the branches with a plastic bag containing moist organic substrate. The following variables were evaluated 120 days after air-layering: percentage of rooted and callused air layers, longest root length, and root dry matter. The analysis of variance indicated no significant differences between the IBA concentrations for all variables, but the rooting percentages were high (68.6 to 92.2%) regardless of the application of the exogenous auxin.